Stage predictivity of neutrophil/lymphocyte and platelet/lymphocyte ratios in pancreatic neuroendocrine tumors - Dikmen, Kürşat (Turk J Surg, 2020)
OBJECTIVES: This study aimed to analyze the correlations between European Neuroendocrine Tumor Society (ENEST), Tumor Node Metastasis (TNM) staging systems and pre-operative neutrophil/lymphocyte (NLR) and platelet/lymphocyte ratios (PLR) in patients with pancreatic neuroendocrine tumor (PNET). MATERIAL AND METHODS: Forty-four patients with diagnosed PNET were analyzed retrospectively. Accordingly, the patients’ blood and clinicopathological parameters were analyzed. The correlations between laboratory parameters and tumor stages were evaluated using Eta correlation analysis. The control group was composed of volunteering healthy participants who had similarities with our study group as regards age and gender. RESULTS: According to ENETS classification, 34% of the patients were stage I, 25% were stage II, 20.4% were stage III and 20.4% were stage IV. NLR and PLR mean values were 2.4 and 127, respectively. NLR values of the patients in the study group were higher than those of the control group (p= 0.001). NLR and PLR values of stage I, II, III and IV patients tended to increase in parallel to the higher stages according to ENETS system (p= 0.0001 and p= 0.0001, respectively). Similarly, NLR and PLR values increased in parallel to the higher stages according to TNM system (p= 0.0001 and p= 0.0001, respectively). In addition, NLR values were found to be higher in patients with lymph node metastasis than in those without (p= 0.001). CONCLUSION: Increased levels of inflammatory mediators such as NLR and PLR are associated with advanced stages of patients with PNET.